Identification of Interest Rates and International Capital Flows - Haynes, Stephen E. (The Review of Economics and Statistics, 1988)
The conventional paradigm that capital movements respond to differences in interest rates between countries and simultaneously reduce interest-rate differentials has been difficult to demonstrate empirically. This paper argues that such a demonstrati on may be feasible if a simultaneous model is specified that describe s the dynamics of adjustment and if a data interval is chosen that re veals the dynamics. Examination of U.S. and Canadian data from the 19 60s supports the argument-with monthly observations, that paradigm is strongly supported; with quarterly observations, capital flows and i nterest rates are not significantly related. Copyright 1988 by MIT Press.